The quality of patients chronic rhinosinusitis after functional endoscopicsinus surgery at Dr Sardjito General Hospital, Yogyakarta, Indonesia - Wahyu Dwi Kusdaryanto; Windarti Isminarsih; Luh Putu Lusy Indrawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Chronic Rhinosinusitis (CR) is disease by incidence and prevalence of high and is expected to rise to load against the economy and lowering the quality of life of patients.with CR involved many factors and an impact of highly significant on the quality of life and affect the economy.The quality of life patients done to assess the effects and result of surgery.Sino nasal outcome test-20 ( snot-20 ) was one of the instruments specific measurement the quality of life of patients CR. 10 patients who surgery action , obtained improving the quality of life based on snot-20 observed 28 days after done the act of surgery. Rate the SNOT- 20 before surgically obtained 37,3 with DS ± 7,87 and 28 days after done surgically obtained rata-rata snot-20 is 6 with DS ± 2,49. The SNOT-20 pre and post action there are different of significant (p = 0,024 ) .